Konsep Fuqarā’ dalam Al-Qur’an Kajian Semantik Qur’ani - Muhammad Haratullisan; Bashori (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Bima, 2026)
This study aims to analyze the concept of fuqarā’ in the Qur’an through the Qur’anic semantic approach developed by Toshihiko Izutsu. The main problem addressed in this research stems from the tendency to reduce the meaning of fuqarā’ to merely material poverty, whereas the Qur’an presents a broader and more complex conceptualization of poverty. This research employs a library research method, utilizing primary data in the form of Qur’anic verses containing derivatives of the root faqr, and secondary sources including classical Arabic lexicons, Qur’anic exegesis, and works on Qur’anic semantics. The analysis is conducted through four stages: identifying the basic meaning, examining relational meanings, constructing the semantic field, and reconstructing the Qur’anic worldview (weltanschauung). The findings reveal that etymologically, the term fuqarā’ originates from the notion of “lack” or “essential need,” which undergoes semantic transformation within the Qur’anic context. Relationally, fuqarā’ is not only associated with social terms such as miskīn, but also stands in theological opposition to ghaniyy (self-sufficient), reflecting the relationship between humans and God. Within the Qur’anic semantic field, poverty is structured as part of a network of concepts indicating varying degrees of human conditions, both material and spiritual. This study concludes that poverty in the Qur’an is not merely an economic condition, but also represents the ontological dependence of human beings on God and serves as a foundation for the development of social ethics in Islamic society.